Investigation of the Usage Properties of Steel Slag as Pigment in Low-Temperature Glaze - Muhterem Koç; Eda Taşçı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The evaluation of industrial wastes in the ceramics industry has been the subject of research studies in recent years. This study investigated the use of steel slag as a colouring pigment in ceramic glazes. The colour effects of 45 compositions created with a triple-phase diagram with steel slag, CoO, and Cr2O3 on low-temperature glaze composition were determined. The microstructural evaluation of the selected colours by SEM and EDX analysis were carried out.The prepared glaze compositions were applied by pouring on the high silica ceramic body. Glazed tiles were sintered in a muffle furnace at 950 ℃ and then L*a*b colour and gloss brightness values were measured. By using steel slags instead of Fe2O3, black glazes were obtained in the triple diagram.